PRODUCTION OF TITANIUM METAL USING HIGH TEMPERATURE ELECTROLYSIS PROCESS: CRITICAL REVIEW - Nigel, Iryano
Titanium is a light, strong, and high corrosion resistant metal. Also, it is the ninth abundant element in the Earth's crust. Titanium is commonly used as a structural material in aircraft and implants. Its superior properties allow titanium to be applied to other fields such as automotive, architecture, and other industries. However, titanium production process is very difficult and complicated, making titanium price very expensive so that titanium utilization is still limited. Nowadays, various processes are developed to replace the current titanium production process (the Kroll process). There are promising electrolysis processes such as the FFC Cambridge process and the MER process, which seem more economical than the Kroll process. In this study, metallurgical aspects of these processes will be studied as well as their application for titanium production in Indonesia. This study begins with the collection of reference documents related to titanium and its production process. Then, documents will be selected based on correlation with the purpose of the study. After that, the selected documents will be analyzed to answer the purpose of this study. Further searching and review from the reference are conducted if there is some unclear information. Lastly, conclusion is drawn based on the conducted literature study and also suggestion for subsequent research. Based on the literature study, it was obtained that: (1) in the FFC Cambridge process, the reduction of titanium oxide at the cathode occurs in several stages at 900 oC. This makes the decomposition potential of titanium oxide increases as the oxygen content decrease. Time variations for the electrolysis also produce different products such as magneli and calcium titanate. The reduction stage of TiO to metal takes the longest time due to the difficulty of oxygen diffusion. (2) In the MER process, the reduction reaction at the cathode occurs in one step. However, the carbothermic reduction of TiO2 has to be controlled with suitable TiO2/C ratio to produce a titanium oxycarbide, whose composition is Ti2CO at 1500 oC. Different compositions of titanium oxycarbide will affect the anode dissolution during electrolysis at 750 oC. (3) Both of these processes require different feed for the electrolysis so that this process can be applied in Indonesia under different conditions.